Varieties of expansionism: A comparative-historical approach to the study of state expansion and state contraction. (June 2019) - Becke, Johannes
Abstract: This article introduces a 'varieties of expansionism' approach to the study of state expansion and state contraction. The approach is based on a comparative-historical typology that distinguishes between four ideal types of state expansion (patronization, satellization, exclavization and incorporation) and four corresponding ideal types of state contraction (depatronization, desatellization, deexclavization and disincorporation). The framework understands the variability and reversibility of state expansions as the reflection of a shifting opportunity structure composed of power resources (deployed by the expanding state) and the level of stateness (within the captured territory). The article illustrates the dynamics of designing, changing and reversing state expansions based on case studies of Israel's security zone in Southern Lebanon (1985–2000), Syria's hegemony over Lebanon after the civil war (1989–2005), Turkish rule over Northern Cyprus (since 1974) and the failed Indonesian capture of East Timor (1975–1999). After discussing the dynamics of institutional change and the categorization of mixed cases, the article argues that the framework might be particularly fruitful for the exploration of territorial conflicts in the wake of decolonization and post-colonial state formation.